Disease incidence and severity in cowpea lines evaluated for resistance to single and multiple infections of endemic viruses in Nigeria - Ogunsola, K.E.; Ilori, C.; Fatokun, C.A.; Boukar, O.; Ogunsanya, P.; Kumar, P. Lava (Informa UK Limited, 2021)
Cowpea (Vigna unguiculata (L.) Walp) is susceptible to several viruses in West Africa. Cowpea viral diseases are mainly controlled through the use of resistant cultivars. Co-infection with more than one virus is frequent in the fields and the resultant synergistic effect often compromises host resistance identified by screening against individual viruses under field or controlled conditions. In this study, eight improved cowpea breeding lines, identified as resistant to single infections and a susceptible cultivar (Ife Brown), were evaluated for their reactions to single and multiple infections of three viruses endemic in West Africa; viz., bean common mosaic virus-blackeye cowpea mosaic strain (BCMV-BlCM), southern bean mosaic virus (SBMV), and cucumber mosaic virus (CMV). Cowpea seedlings were inoculated with these viruses singly or in combination. Disease incidence and severity were recorded at weekly intervals for eight weeks. Virus infection was confirmed by enzyme-linked immunosorbent assay or reverse transcription-polymerase chain reaction. Systemic mosaic, vein-banding, and stunting were observed on inoculated plants. Mixed infection increased symptom severity and the highest severity was found in plants co-infected with CMV. Phenotyping against mixed-infections was more promising for estimating host resistance response in cowpea than single infections. Based on virus incidence and severity, lines IT97K-1069-6 and IT04K-405-5 were found to be resistant to SBMV, whereas IT99K-1060 and IT98K-503-1 were susceptible to the three viruses. IT-98 K-1092-1 was found to be resistant to BCMV and SBMV and tolerant to CMV under mixed inoculation scenario. Cowpea line IT-98 K-1092-1 is, thus, the best resistance source for use in virus resistance-breeding programs.